Identification and cloning of lipase and nucleoside permease enzyme from thermophilic bacteria / Norazwin Norazizi - Norazizi, Norazwin (2013)
Lipase enzymes can be isolated from thermophiles in hot springs. This present study involves the identification and retaining the interested genes by cloning. Previous thermophiles (Al, A3, A4, A5, A6, A8, A13 and A14) which were kept in glycerol stocks were subcultured onto Castenholtz Tryptone Yeast (CTYE) agar for further study. Rhodamine B-olive oil agar plate culture was used to screen for lipase enzyme followed by PCR. Isolates Al, A3, A4 and A5 was a circular, pin point, creamy colonies with entire margin on CTYE media, whilst A6, A8, A13 and A14 was irregular, spreading, wavy, and creamy colonies. Four isolates (Al, A3, A4 and A13) showed the presence of orange fluorescence around colonies on rhodamine B olive oil agar plate thus indicating the presence of lipase. Amplification and sequencing of lipase gene showed that Al, A3, and A4 were 98% similar to Geobacillus and Bacillus sp. compared to other lipase sequences in the GenBank. Interestingly, A14 was 90% similar to nucleoside permease gene from Anoxybacillus flavithermus WK1. A14 was further identified by 16S rRNA gene which showed 93% similarities to Anoxybacillus flavithermus WK1. On further gene-protein translation study, A14 was found to contain an amino acid sequence highly homologous to the putative domain hits to nucleoside permease protein. Lipase gene from isolate Al and nucleoside permease gene from isolate A14 were cloned using pBAD TOPO expression kit cloned. Lipase gene of Al was not successfully cloned; however, the cloning of nucleoside permease gene of A14 was successful and further sequenced and reconfirmed as such. In conclusion, three lipase producing bacteria, Geobacillus spp. (Al, A3, A4) and one nucleoside permease producer, Anoxybacillus sp. (A14) were identified in this study. Lipase and nucleoside permease enzymes are recommended for further characterization and its suitability for industrial usage.